MECHANICAL AND RHEOLOGICAL PROPERTIES OF HIGH-MODIFIED CONCRETE UNDER AXIAL COMPRESSION - and (Municipal economy of cities. Series: «Economy science», 2013)
The results of experimental studies of the characteristics of mechanical and rheological properties of high-strength concrete on the basis of modified organo-modifiers, using industrial waste industry of the Donbass.